Back Cover: Thermo‐Responsive MOF/Polymer Composites for Temperature‐Mediated Water Capture and Release (Angew. Chem. Int. Ed. 27/2020). Issue 27 (14th May 2020) - Karmakar, Avishek; Mileo, Paulo G. M.; Bok, Ivan; Peh, Shing Bo; Zhang, Jian; Yuan, Hongye; Maurin, Guillaume; Zhao, Dan
Abstract : Temperature‐mediated water capture and release in composite materials is described by G. Maurin, D. Zhao, and co‐workers in their Research Article on page 11003 . The thermoresponsive polymer poly( N ‐isopropylacrylamide) (PNIPAM) was introduced into the cavities of the metal–organic framework MIL‐101(Cr) by in situ polymerization of the loaded monomer. The resultant composites show very high water uptake and can release most of the adsorbed water at a slightly elevated temperature as a result of the hydrophilic‐to‐hydrophobic phase transition of the PNIPAM component.